A Study of the Identification Method for the Test Flat Objects Based on Dimensionless Signs of their Contours. (2015) - Sadykov, S.S.; Kulkov, Y.Y.
Abstract: The article is devoted to the experimental study of the possibility to use dimensionless signs of an object binary image contour. The basis for the attribute vectors formation is the characteristics of the image contour. The experiments on the identification of the objects are based on the calculation of standard deviation.